2010
DOI: 10.1021/op100154d
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Challenges of Solid Bridging and Constriction during Pd-Catalyzed C−N Bond Formation in Microreactors

Abstract: We investigate the mechanisms that govern plugging in microreactors during Pd-catalyzed amination reactions. Both bridging and constriction were shown to be important mechanisms that lead to clogging in our system and greatly limited the utility of microsystems for this class of reactions. On the basis of these observations, several approaches were engineered to overcome the challenge of plugging and to enable the continuous-flow synthesis of a biarylamine. Bridging could be eliminated with acoustic irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
208
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(212 citation statements)
references
References 69 publications
2
208
1
1
Order By: Relevance
“…Another example of the d f impact on the operation stability of industrial units, is represented by product or by-product crystallization in microreactors, which leads to reactor clogging, of particular importance given the small reactor diameter (in the range of 10-1000 μm) [84]. The fractal dimension of the formed crystals plays a key role in this process as a low d f will cause a faster clogging.…”
Section: Coagulum Formation In Industrial Production Unitsmentioning
confidence: 99%
“…Another example of the d f impact on the operation stability of industrial units, is represented by product or by-product crystallization in microreactors, which leads to reactor clogging, of particular importance given the small reactor diameter (in the range of 10-1000 μm) [84]. The fractal dimension of the formed crystals plays a key role in this process as a low d f will cause a faster clogging.…”
Section: Coagulum Formation In Industrial Production Unitsmentioning
confidence: 99%
“…In contrast, in our opinion, mini-/mesoscale reaction and separation technology (mm−cm scale) have received relatively less attention, even though it is potentially possible to access some of the advantages of small scales while lowering the sensitivity to practical problems such as blockages from solids in suspension, which still form a main limitation for microreaction technology. 5, 15 Furthermore, it has been observed that fluid distribution and parallelization of microscale units is not such a straightforward task, despite expectations based on the standard scaling-out principles. 16 Thus, constructing basic units at a moderately larger scale should theoretically make scaling-up/-out an easier and smoother task.…”
Section: Introductionmentioning
confidence: 99%
“…66 More trivially, clogging can be hindered by employing wide bore channels or tubing, as well as applying agitation or sonic irradiation and controlling of fluid velocity. 25,27,67 If clogging is caused by the crystallization of low melting substances, the heating of the problematic areas is an effective method. 39 In the gas-liquid two phase flow during an ozonolysis leading to drug candidate OZ439, the evaporation of the liquid phase caused clogging.…”
Section: Ensuring Stability For Continuous Productionmentioning
confidence: 99%